Developing Operation Rules for Reservoirs in the Upper Da River Basin Using Multi-source Remote Sensing Data - Van Hai, Khuong; Ba Huy, Dao; Tien Giang, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2025)
In transnational river basins, upstream hydropower projects and multipurpose reservoirs have a strong impact on downstream flow regimes, directly affecting agricultural production, fisheries, waterway transport, water security. and environmental and ecological issues. The challenge is that most upstream countries do not fully disclose reservoir operation data. This paper presents the method and results of applying multi-source remote sensing data (Sentinel-1, Sentinel-2, DEM) to restore and update reservoir parameters as well as reservoir operation parameters in the upper Da River basin. Integrating the parameters into the VIC-RES model has significantly improved the quality of simulated streamflow to Lai Chau Reservoir in Vietnam. Specifically, the NSE evaluation indicators increased from 0.59 to 0.83–0.84; Pbias decreased from 40% to 15–19%; KGE increased from 0.54 to 0.72–0.73. The proposed method not only improves the performance of the simulation model but also provides a feasible approach for transboundary water resources management and can be extended to many other basins.